2010
DOI: 10.1038/ja.2010.23
|View full text |Cite
|
Sign up to set email alerts
|

Survey for β-lactamase among bacterial isolates from Guangzhou, China hospitals between 2005–2006

Abstract: The b-lactamase genes, which confer multi-drug resistance, are spreading among clinical bacterial isolates. As part of a routine surveillance program, we collected 302 bacilli isolates between June 2005 and October 2006 from four hospitals in Guangzhou, China. The isolates were screened for multidrug resistance and for the presence of b-lactamases. In all, 80 isolates were identified as multidrug-resistant with the K-B method. These isolates were phenotypically screened for b-lactamase activity by disk diffusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…The strains were also analyzed for the presence of other major beta-lactamase genes ( bla CTX-M , bla SHV , bla TEM ), plasmid mediated quinolone resistance (PMQR) determinants ( qnr A, qnr B and qnr S), sulfonamide resistance genes ( sul I and sul II) and tetracycline resistance genes ( tet A and tet B) [7, 1722]. To define the mechanism of transmission of the pAmpC gene, we screened bla ampC for the insertion sequence ISE cp 1 by ISE cp 1- bla CMY linkage PCR [23]. Strains positive for this PCR were sequenced as previously described.…”
Section: Methodsmentioning
confidence: 99%
“…The strains were also analyzed for the presence of other major beta-lactamase genes ( bla CTX-M , bla SHV , bla TEM ), plasmid mediated quinolone resistance (PMQR) determinants ( qnr A, qnr B and qnr S), sulfonamide resistance genes ( sul I and sul II) and tetracycline resistance genes ( tet A and tet B) [7, 1722]. To define the mechanism of transmission of the pAmpC gene, we screened bla ampC for the insertion sequence ISE cp 1 by ISE cp 1- bla CMY linkage PCR [23]. Strains positive for this PCR were sequenced as previously described.…”
Section: Methodsmentioning
confidence: 99%
“…These results indicate that β-lactamase is the main resistance mechanism to cephalexin among these isolates. β-lactamase is produced in a wide range of Gram-positive and Gram-negative bacteria with great variety of chemical, physical and enzymological properties (Doran et al 1990;Toroglu et al 2005;Liao et al 2010). However, bacterial isolates No.…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that (7.3%) of the tested isolates were beta-lactamase producers. This suggests possible abuse of these drugs, poor hospital attendance and the need for better enlightenment campaign against the use of drug without prescription [17] .In a recent study in China about 26.4% had a β-lactamase phenotype,the β-lactamase genes, which confer multi-drug resistance, are spreading among clinical bacterial isolates [18]. Increase in the beta-lactamase producing S. aureus and E. coli was above 80%.The increasing in prevalence of microorganism, particularly of beta-lactamase producing E. coli and S. aureus and ESLB is alarming situation [19].…”
Section: Resultsmentioning
confidence: 99%